Electroosmotic flow in a microchannel packed with microspheres - Kang, Yuejun (2008)
The electrokinetic (EK) micropump, which employs electroosmosis rather than hydrostatic pressure, is a rapidly emerging pumping technique to transport reagents and electrolytes through microchannel networks.